KINERJA PEGAWAI DI BADAN PENGELOLA KEUANGAN DAERAH (BPKD). DALAM PENGELOLAAN ASET DAERAH DI KABUPATEN ENREKANG - Adelina, Rika; Madani, Muhlis; Burhanuddin, Burhanuddin (Universitas Muhammadiyah Makassar, 2023)
The purpose of this study was to find out the quality of work, work quantity, implementation of duties and responsibilities of employees at the Regional Financial Management Agency (BPKD) in Regional Asset Management. This study used quantitative data using primary and secondary data. The population of this study was 30 people and the samples in this study were all of the population. In this study, data collection techniques were carried out using several methods, including observation and questionnaire. The results of this study showed the quality of work with 3 indicators, namely quality work , In accordance with user expectations and Accurately and honestly getting the results of data processing showing an average score of 3.58 Quantity of work with 2 indicators, namely the amount of work and achievement targets showing an average score of 3.59 for variable implementation of tasks with 2 indicators, namely employee duties and work time discipline. employees got the results of data processing that showed an average score of 3.44 the variable of work employee responsibility with 3 indicators namely employee commitment, an honest employees and employee motivation got from the results of data processing that showed an average score of 3.51, from these variables it produced results in Regional Asset Management Agency office in Enrekang Regency was very good.